Description of a new species of Tilapia Smith, 1840 (Teleostei: Cichlidae) from Ghana - Dunz, Andreas R.; Schliewen, Ulrich K. (Zootaxa, 2010)
A new species of the genus Tilapia Smith, 1840 is described from the Pra River drainage in Ghana. Tilapia pra sp. nov. is distinguished from all Tilapia species except T. sparrmanii, T. ruweti, T. guinasana, T. baloni, T. brevimanus, T. mariae, T. cabrae and T. busumana in having bicuspid posterior pharyngeal teeth on the lower pharyngeal jaw. It differs from T. baloni and T. ruweti in having more gill rakers on the first ceratobranchial (lower) gill-arch (10–12 vs. 6–9), from T. guinasana in having a higher number of upper lateral line scales (18–22 vs. 14–17) and from T. sparrmanii in a combination of a higher number of upper lateral line scales (18–22 vs. 14–19), a shorter anal fin base (15.0–18.6% vs. 18.0–23.8% of SL) and a lower number of vertical stripes (6–7 vs. 8–9). It differs from T. mariae, T. cabrae and T. brevimanus in having robust, non-spatulate outer row jaw teeth (vs. gracile spatulate teeth) and from T. busumana in having a longer last dorsal-fin spine (16.2–21.3% vs. 11.6–14.9% of SL), and a smaller lower lip length (8.0–10.7% vs. 9.6–13.9% of SL) and lower jaw length (9.9–13.6% vs. 10.5–15.2% of SL). In addition, T. pra sp. nov. differs from T. busumana in ground coloration. T. pra sp. nov. possesses a light brown to greyish dorsum and a beige to yellow ventral area vs. a bluish-purple to blackish dorsum and darker on underside of head and body of T. busumana.